Evaluación de la planificación colaborativa de la cadena de suministro en la agroexportadora y comercializadora junipertree cía ltda - Loor Zamora, Fatima Enedicta (2017)
The present research evaluated the collaborative planning of the supply chain in the commercialization JUNIPERTREE CÍA LTDA, for the characterization of the variables that are inconsistent with the company and do not contribute to the development and growth of the same. For the execution of the case study, four phases were established, which began with a situational diagnosis of the organization, in order to identify weaknesses, strengths, opportunities and threats, in which a SWOT matrix was determined as an improvement contribution ; Variables were also integrated to generate survey models, interview, applied to the manager, employees and shareholders. As a result, the data were tabulated using statistical graphical techniques, which show the results of the average value per question; Then the tool to be used was the checklist for measuring the level of collaborative planning, using the analytical method of hierarchy SAATY, ending with the elaboration of an improvement plan using the results of the list of Check for identification in affected areas. The evaluation of collaborative planning of the supply chain required a quantitative, qualitative, analysis - synthesis methodology, the same one that helped to generate the respective results, in relation to these the lowest level and that needs to improve, was the variable of Collaborative replenishment, identified specifically in the area of inventory management, procurement, suppliers and merchandise distribution.